2007
DOI: 10.1080/03008200601166160
|View full text |Cite
|
Sign up to set email alerts
|

Wound Healing in Tenascin-X Deficient Mice Suggests that Tenascin-X is Involved in Matrix Maturation Rather than Matrix Deposition

Abstract: Tenascin-X (TNX) is an extracellular matrix glycoprotein whose absence in humans leads to a recessive form of Ehlers-Danlos Syndrome (EDS). TNX deficient patients have hypermobile joints and fragile skin, but unlike the classical type of EDS, no atrophic scars were observed. Anecdotal evidence suggested that wound healing in TNX deficient patients is abnormal, but no detailed study has been performed so far. To address the role of TNX in wound healing, we analyzed skin wound morphology and mechanical propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 28 publications
0
45
0
2
Order By: Relevance
“…Also, TNXB was shown to be hypomethylated in dcSSc and lcSSc-FB [12]. TNXB encodes a member of the tenascin family of extracellular matrix glycoproteins, which are involved in matrix maturation [14]. These observations indicate that methylation status of the collagen and ECM proteinencoding genes is intimately involved in ECM accumulation in SSc.…”
Section: Aberrancies Of Dna Methylation In Collagen Andmentioning
confidence: 90%
“…Also, TNXB was shown to be hypomethylated in dcSSc and lcSSc-FB [12]. TNXB encodes a member of the tenascin family of extracellular matrix glycoproteins, which are involved in matrix maturation [14]. These observations indicate that methylation status of the collagen and ECM proteinencoding genes is intimately involved in ECM accumulation in SSc.…”
Section: Aberrancies Of Dna Methylation In Collagen Andmentioning
confidence: 90%
“…49 Interestingly, the genetic background markedly influences EDS manifestations, as the phenotype was less severe on a homogenous (C57BL/6) compared to a mixed (129/SvJ, C57BL/6 and FVB) genetic background. 29,47,49 One possible Indirect immunofluorescence of TN-X performed on cryostat sections of mouse skin after incisional wound (*). TN-X was detected using polyclonal antibodies directed against the bovine TN-X FNIII b9-b10 repeats.…”
Section: An Architectural Function Illustrated By the Ehlersdanlos Symentioning
confidence: 99%
“…37 It is also conceivable that TN-X might be involved in elastic fibers formation and maturation. 29,58 Figure 3. Model of TN-X integration within the collagenous network.…”
Section: An Architectural Function Illustrated By the Ehlersdanlos Symentioning
confidence: 99%
See 1 more Smart Citation
“…Ehlers-Danlos Syndrome is characterized as hyperextensible skin and joints, susceptibility to bruising, and poor wound healing. The role of tenascin-X in this syndrome, which previously was believed to be limited to collagens and enzymes that Tenascin-X Ehlers-Danlos Syndrome-related phenotypes Abnormal epidermal scars, hyperextensible skin, fragile skin, reduced dermal fibrillar collagen, abnormal fibrillar collagen Mao et al 2002;Minamitani et al 2004aMinamitani et al , 2004bEgging et al 2006Egging et al , 2007 Miscellaneous phenotypes Abnormal vaginal plug location, rectal prolapse Egging et al 2008 Abnormal accumulation of dermal lipids Matsumoto et al 2004 Abnormal melanoma growth and metastasis Matsumoto et al 2002 help modify and assemble collagens, was shown convincingly by the phenotype of the tenascin-X knockout mouse (Table 3) (Mao et al 2002; see also Egging et al 2006). These mice have easily deformable skin and a significant decrease in the number of collagen fibrils in the dermis.…”
Section: Morellini and Schachner 2006mentioning
confidence: 99%